Establishment of a dynamic nomogram including thyroid function for predicting the prognosis of acute ischemic stroke with standardized treatment - Jiang, Yi; Xie, Chunhui; Zhang, Guanghui; Liu, Mengqian; Xu, Yiwen; Zhong, Wen; Ge, Zhonglin; Tao, Zhonghai; Qian, Mingyue; Gong, Chen; Shen, Xiaozhu (Frontiers in Neurology, 2023)
Purpose Many patients with acute ischemic stroke (AIS) cannot undergo thrombolysis or thrombectomy because they have missed the time window or do not meet the treatment criteria. In addition, there is a lack of an available tool to predict the prognosis of patients with standardized treatment. This study aimed to develop a dynamic nomogram to predict the 3-month poor outcomes in patients with AIS. Methods This was a retrospective multicenter study. We collected the clinical data of patients with AIS who underwent standardized treatment at the First People's Hospital of Lianyungang from 1 October 2019 to 31 December 2021 and at the Second People's Hospital of Lianyungang from 1 January 2022 to 17 July 2022. Baseline demographic, clinical, and laboratory information of patients were recorded. The outcome was the 3-month modified Rankin Scale (mRS) score. The least absolute shrinkage and selection operator regression were used to select the optimal predictive factors. Multiple logistic regression was performed to establish the nomogram. A decision curve analysis (DCA) was applied to assess the clinical benefit of the nomogram. The calibration and discrimination properties of the nomogram were validated by calibration plots and the concordance index. Results A total of 823 eligible patients were enrolled. The final model included gender (male; OR 0.555; 95% CI, 0.378–0.813), systolic blood pressure (SBP; OR 1.006; 95% CI, 0.996–1.016), free triiodothyronine (FT3; OR 0.841; 95% CI, 0.629–1.124), National Institutes of Health stroke scale (NIHSS; OR 18.074; 95% CI, 12.264–27.054), Trial of Org 10172 in Acute Stroke Treatment (TOAST; cardioembolic (OR 0.736; 95% CI, 0.396–1.36); and other subtypes (OR 0.398; 95% CI, 0.257–0.609). The nomogram showed good calibration and discrimination (C-index, 0.858; 95% CI, 0.830–0.886). DCA confirmed the clinical usefulness of the model. The dynamic nomogram can be obtained at the website: predict model (90-day prognosis of AIS patients). Conclusion We established a dynamic nomogram based on gender, SBP, FT3, NIHSS, and TOAST, which calculated the probability of 90-day poor prognosis in AIS patients with standardized treatment.